The Olympic Games: The Experience of a Lifetime or Simply the Most Important Competition of an Athletic Career? - Jensen Rune Dall; Christiansen Ask Vest; Henriksen Kristoffer (Sciendo, 2014)
As a multi-sport event that only takes place every four years and is accompanied by intense media coverage, the Olympic Games are often described by athletes as a defining moment in their careers. The objectives of the present study were: 1) to describe differences in expectations of Olympic debutants towards the Olympics and their actual experiences while they were at the Games; and 2) to describe how the athletes negotiate the balance between performing at and enjoying the experience of the Olympic Games. Further, we will discuss the athletes' stories in light of the differences between the goals and expectations of the elite sport system and those of the individual athletes. Data was collected through a qualitative interview study with a pre- and post-Olympic competition design.